PLASMA NUTFAH BABI BALI MUTIARA YANG TERPENDAM - Suarna, I Wayan; Suryani, N.n.; Trisnadewi, A.A. A.S. (Bumi Lestari; Vol 15 No 2 (2015), 2016)
Millennium Development Goals has been mandated to always strived to reduce therate of loss of biodiversity as a very valuable genetic resources. Bali swine germplasmwhose condition is increasingly threatened by the inclusion of various types of pigs thathave the ability to produce more meat. Last post five years, Bali’s pig population in theprovince of Bali continued to decline and reached until 30 percent (243 310 head) of allpigs in Bali (817 489 head). Of the pig population in Bali as much as 53 percent in Buleleng.Bali pig role in socio-cultural activities and opportunities to explore the culinary marketrequires no effort to increase productivity in a sustainable pig Bali. Various strategicapproach to the development and preservation of pig Bali described in this paper as aneffort to accelerate the achievement of the millennium development.
Keywords: Bali pigs, the rate of extinction, conservation, genetic resources.